A polydopamine coating ultralight graphene matrix as a highly effective polysulfide absorbent for high-energy LiS batteries. (October 2016) - Zhou, Lan; Zong, Yun; Liu, Zhaolin; Yu, Aishui
Abstract: The soft polydopmine (PDA) layer with polar functional group was coated onto the ultralight graphene sheets (HRG) using a simple approach in a mixture of ethanol and water solution. Sulfur was further dispersed onto the surface of PDA-HRG sheets by S/CS2 solution impregnation method to obtain PDA-HRG/S composite as the cathode material for lithium sulfur batteries. The resulting composites are characterized by SEM, TEM, XRD and so on. The ultralight graphene matrix could improve the conductivity of the electrode and offer a large surface for deposition of sulfur, while the coating of hydrophilic soft PDA layer can adsorb polar polysulfides on-site and accommodate the volume change of S during the discharging processes, resulting in an excellent electrochemical performance. Highlights: PDA with polar functional group was coated onto the surface or interspace of ultralight graphene sheets. PDA layer are used as bifunctional materials for adsorption agent and buffer. The PDA-HRG/S electrode shows outstanding cycling stability and rate capability.